2016
DOI: 10.1111/cge.12747
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a founder BRCA1 mutation in the Moroccan population

Abstract: Breast cancer (BC) is the most frequent cancer among women in Morocco. However, the role of the most prevalent BC-predisposing genes, BRCA1 and BRCA2, has been largely unexplored. To help define the role of BRCA1 in BC in Morocco, we characterized the first potential BRCA1 founder mutation in this population. Genetic testing of BRCA1 and BRCA2 in BC high-risk families identified mutation BRCA1 c.5309G>T, p.(Gly1770Val) or G1770V in five independent families from Morocco, suggesting a founder effect. To confirm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…Another novel founder, BRCA2 mutation, was identified by var der Merwe et al ( 53 ) in the Bantu-speaking Xhosa population (South Africa). Other studies have identified new BRCA mutations and their contribution to early-onset and sporadic breast and/or ovarian cancer in Arabic speaking countries ( 57 ) of Egypt ( 58 ), Tunisia ( 51 , 59 66 ), Algeria ( 67 69 ), Morocco ( 70 72 ), and Sudan ( 73 , 74 ), in addition to Senegal ( 75 ), Mauritius ( 76 ) and South Africa ( 50 , 77 79 ) in the Sub-Saharan region.…”
Section: Resultsmentioning
confidence: 99%
“…Another novel founder, BRCA2 mutation, was identified by var der Merwe et al ( 53 ) in the Bantu-speaking Xhosa population (South Africa). Other studies have identified new BRCA mutations and their contribution to early-onset and sporadic breast and/or ovarian cancer in Arabic speaking countries ( 57 ) of Egypt ( 58 ), Tunisia ( 51 , 59 66 ), Algeria ( 67 69 ), Morocco ( 70 72 ), and Sudan ( 73 , 74 ), in addition to Senegal ( 75 ), Mauritius ( 76 ) and South Africa ( 50 , 77 79 ) in the Sub-Saharan region.…”
Section: Resultsmentioning
confidence: 99%
“…13 In Africa, founder mutations have been reported in Yoruba population from Nigeria (c.303T>G; (p.Tyr101Ter)) in a series of four families, 13 in Afrikaners from South Africa (c.2641G>T (p.Glu881Ter)) 14 in five families, and in Morocco (c.5309G>T; (p.Gly1770Val)) in five families. 11 The founding effect of the variant c.815_824dup10 was reported first in five nonrelated families from US 20 and the mutation was supposed to be of West African origin.…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1 c.5266dup and, c.181 T > G as well the Ashkenazi Jewish founders are all present in the groups of low or moderately frequent mutations in our study. A recently identified Moroccan BRCA1 variant has been demonstrated in three families at OUH and have been shown to share the same haplotype as in a series of Moroccan patients [ 23 ]. Systematic collection of information on geographic or ethnic origin per individual/family was beyond the scope and permits of this study, but was performed in 2007, where it was found to be an apparent geographical connection for some of the frequent mutations in BRCA1 and BRCA2 [ 17 ] .…”
Section: Discussionmentioning
confidence: 99%